On the possibility of embryo donation in Hispanic America - Álvarez-Díaz, Jorge Alberto (2009)
Empirical studies regarding embryo donation in developed countries show that the most probable action would be to discard surplus embryos and, if they would donate them, the preferred option would be for research, and eventually to other couples. There are not enough studies in Hispanic America about the opinions of those who have participated in assisted reproductive technologies (ART) regarding embryo disposition of surplus embryos. Moreover, there are scarce specific laws regulating ART in order to contrast people’s opinion. Works performed in Ecuador, Chile and Peru are also preceding works and basis to design a Latin American Study on embryo donation. It is necessary to perform a descriptive study on Latin American couples opinions regarding embryo donation, which would benefit several areas (clinical practice, research, bioethics, biolaw, etc.).